STRATEGI PEMERINTAH DALAM PENEMBANGAN TELEKOMUNIKASI BERBASI INTERNET DI DESA TANA TORO - Rahmawati; Hamid, Hariyanti; Sellang, Komarudding (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to reveal how much government procedures are involved in developing the internet network in Tana Toro Village. The research method used in this research is a qualitative method. Data was collected using reviews, interviews, photo sessions and field notes with Nvivo 12 plus data analysis.This research shows that the government's strategy in developing internet-based telecommunications is already visible in the form of building towers. Even though there are still shortcomings and weaknesses in telecommunications development, namely road infrastructure which is caused by geographical location which is not possible so it cannot be said to be good, internet-based telecommunications development facilities are clearly visible and there are several factors that influence the government's strategy in developing internet-based telecommunications, namely Electrical Services. PLN and Road Infrastructure are still slippery and muddy when it rains with geographical conditions that are quite sloping so they are prone to landslides.